The Impact of Pre-Marriage Pregnancy Mediatization in The Social Media To Indonesians Morality Hierarchy - Jalaluddin Basyir; Ade Sukmawati (Universitas Teknologi Yogyakarta, 2021)
Social media has greatly transformed humans' perspectives into amoral behavior. Thus, pre-marriage pregnancy, long-term deviant morality, has been more considerably admissible. This study aims to explore how social media has mediatized immorality to be more reasonable. This study uses a content analysis approach that relies on the ontology hermeneutics of Hans-Georg Gadamer. It is used to analyze and comprehend the implicit meanings of young Indonesian celebrities' pre-marriage pregnancy revealed on YouTube. Such perceived immorality shifts and reshapes the public's notion of morality value. The most important consideration is social media mediatization. Mediatization could inherently restructure social reality and moral values for the new social-cultural paradigm matrix's media logic. The shift of social morality hierarchy is the most significant consequence, which is no longer imperative in pre-marriage pregnancy. It impacts morality structures that could be a new authority to challenge social-cultural tradition in expressing morality. It implies that the government should design regulations or policies to counteract those cases and get the public involved in media literacy.